Strategi Bersaing Perguruan Tinggi Menghadapi Liberalisasi Pendidikan - M. Suyanto (Unisia, 2006)
The liberalization of education will be equal to the liberalization of economy because it implies on the investors profit of international of education. The entering of foreign universities will increase competitive advantage og Indonesian universities. The competitive strategy is very rigid that causes the bloody ocean for those universities. This strategy will be called Bloody or Red Ocean strategy. To avoid this rigid competitive, there are three effective mutual effects:focus, move to avoid, and main motto. Besides, there are the relation between analysis techniques and six principles i formulating and applying the Blue Ocean Strategy will make the universities in Indonesia survive.